Rapid Diagnosis of Recurrent Paucibacillary Tuberculosis - Claudia Jafari; Ioana Diana Olaru; Franziska Daduna; Christoph Lange; Barbara Kalsdorf (Case Western Reserve University, 2023)
Introduction: The rapid diagnosis of tuberculosis recurrence can be challenging due to persistently positive detection of Mycobacterium tuberculosis-specific DNA from sputum and bronchopulmonary samples in the absence of active disease. Methods: We compared the diagnostic accuracy of the detection of M. tuberculosis-specific DNA by either Xpert (January 2010-June 2018) or Xpert Ultra (July 2018-June 2020) and M. tuberculosis-specific ELISPOT in bronchoalveolar lavage (BAL) samples with M. tuberculosis culture results from sputum or bronchopulmonary samples in patients with suspected recurrence of pulmonary tuberculosis.  Results: Among 44 individuals with previous tuberculosis and a presumptive diagnosis of recurrent pulmonary tuberculosis, 4/44 (9.1%) were diagnosed with recurrent tuberculosis by culture. DNA of M. tuberculosis was detected by Xpert in BAL fluid in 1/4 (25%) individuals with recurrent tuberculosis and in 2/40 (5%) cases with past tuberculosis without recurrence, while BAL-ELISPOT with a cut-off of >4,000 early secretory antigenic target-6-specific or culture filtrate protein-10-specific interferon-γ-producing lymphocytes per 1 million BAL-lymphocytes was positive in 4/4 (100%) individuals with recurrent tuberculosis and in 2/40 (5%) cases of past tuberculosis without recurrence.  Conclusion: M. tuberculosis-specific BAL-ELISPOT is more accurate than BAL-Xpert for the diagnosis of paucibacillary tuberculosis recurrence.